Diary of a wombat - French, Jackie; Whatley, Bruce (New York : Clarion Books, 2003)
In his diary, a wombat describes his life of eating, sleeping, and getting to know some new human neighbors.
First published: Australia : Angus & Robertson, 2002.
Notable/Best Books (A.L.A.)
School Library Journal
Wilson's Children
3.6
K-3.
Keywords: Wombats -- Juvenile fiction; Diaries -- Fiction; Wombats -- Fiction; Diaries -- Fiction; Wombats -- Fiction